2010
DOI: 10.1111/j.1440-1584.2010.01129.x
|View full text |Cite
|
Sign up to set email alerts
|

Availability of antidotes for the treatment of acute poisoning in Queensland public hospitals

Abstract: Most Queensland hospitals stocked some important antidotes, but few had sufficient stock to treat a 70-kg patient or acquire an antidote within the recommended time frame of 30 min. Specific antidote stocking guidelines might be required for Queensland hospitals. A formalised program for stock rotation with rural facilities should be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 18 publications
2
27
0
1
Order By: Relevance
“…This situation is similar to that described in the literature, in which larger hospitals generally have larger, more diversified antidote stocks. 2,5,6 Since no Brazilian recommendations for antidote supply are available, the diagnosis provided by the present study was based on international guidelines. Although the US and UK guidelines for antidote stockpiles can provide a useful starting point, the recommendations may not be realistic from a clinical or economic perspective within our context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This situation is similar to that described in the literature, in which larger hospitals generally have larger, more diversified antidote stocks. 2,5,6 Since no Brazilian recommendations for antidote supply are available, the diagnosis provided by the present study was based on international guidelines. Although the US and UK guidelines for antidote stockpiles can provide a useful starting point, the recommendations may not be realistic from a clinical or economic perspective within our context.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Various factors have been correlated with antidote unavailability, including product shelf-life, the high cost of certain antidotes, the classification of some antidotes as orphan drugs (i.e. drugs of low commercial interest that qualify for incentives such as tax relief, depending on each country's policy) and difficulty in importing antidotes from certain countries.…”
Section: Introductionmentioning
confidence: 99%
“…A despeito da importância dos antídotos e medicamentos usados em intoxicações, diagnós-ticos anteriores apontam para falhas no abastecimento desses em diferentes contextos 4,5,6,7,8,9 . Vários fatores estão associados a esse cenário, incluindo o custo e a necessidade de manutenção de estoques mínimos, que frequentemente vêm a perder validade e precisam ser repostos 8 .…”
Section: Introductionunclassified
“…1 Several studies have reported that hospital pharmacies have inadequate stocks of antidotes available. [2][3][4][5][6] Administration and dosing errors have also been reported in the literature. 7,8 With new dosing strategies being introduced, use in special populations, expanded indications for established antidotes, and the reassessment and expansion of off-label indications for other medications, knowledge of antidotes remains paramount.…”
mentioning
confidence: 99%